2014
DOI: 10.4103/0974-8490.122912
|View full text |Cite
|
Sign up to set email alerts
|

Effect of standardized aqueous extract of Withania somniferaon tests of cognitive and psychomotor performance in healthy human participants

Abstract: Background:Withania somnifera is an herbal medicine that has been known to possess memory-enhancing properties. The current study involved an assessment of cognitive and psychomotor effects of Withania somnifera extract in healthy human participants.Materials and Methods:In this prospective, double-blind, multi-dose, placebo-controlled, crossover study, 20 healthy male participants were randomized to receive 250 mg two capsules twice daily of an encapsulated dried aqueous extract of roots and leaves of Withani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 7 publications
4
39
0
2
Order By: Relevance
“…In terms of safety, no major adverse events were reported in any of the trials, and in a 29‐day study, no biochemical abnormalities (complete blood count, renal function, liver function tests, and lipid profile) were found at the end of study period (Pingali, Pilli, & Fatima, ).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of safety, no major adverse events were reported in any of the trials, and in a 29‐day study, no biochemical abnormalities (complete blood count, renal function, liver function tests, and lipid profile) were found at the end of study period (Pingali, Pilli, & Fatima, ).…”
Section: Resultsmentioning
confidence: 99%
“…The study showed significantly improved reaction time in 5 of the 6 psychomotor performance tests. Withania somnifera brings significant changes in neurological baseline functions as Sitoindosides VII-X and Withaferin A (glycowithanolides) increase cortical muscarinic acetylcholine capacity, with a modulation of cholinergic neurotransmission 44 . A double-blind, placebocontrolled comparative clinical study of effects of Withania somnifera, Panax ginseng, and placebo on psychomotor performance in 30 healthy participants concluded that there was significant improvement in sensorimotor function, auditory reaction time, and mental arithmetic ability 45 …”
Section: Human Studymentioning
confidence: 99%
“…In a very recent study, it is found that W. somnifera at 40 mg/kg significantly reduces the depression in various experimental models (Jayanthi et al, 2012). Clinical trials with healthy volunteers also revealed that aqueous extracts of W. somnifera improve the psychomotor performances in anxiety and depression (Pingali et al, 2014). It was assumed that W. somnifera reduces the production of nitric oxide in the brain tissues, resulting in its anxiolytic activity (Khan and Ghosh, 2011;Maity et al, 2011).…”
Section: Antidepression and Antianxiety Activitymentioning
confidence: 99%